The effects of staffing practices on safety and quality of perioperative nursing care – an integrative review - Nijkamp, Nick; Foran, Paula (Operating Room Nurses Association of Canada Journal, 2024)
Problem identification: Patients undergoing invasive procedures are highly vulnerable to adverse outcomes. From 2012 to 2013, 5.5 per cent of all inpatient admissions reported an adverse event. Perioperative nurses play an important role in providing safe patient care and acting as the patient advocate. This review of literature aims to examine the effects of perioperative staffing and patient safety. Three common staffing themes that impact the safety and quality of patient care were identified; namely, nurse-to-patient ratios, staff training and staff fatigue. Literature search: An integrative literature search to identify empirical data surrounding perioperative nursing staffing was conducted via the use of databases which included CINAHL, JBI, Medline and PubMed. Duplicates were removed, and the preferred reporting items for systematic reviews and meta-analysis (PRISMA) guidelines were followed. A total of 216 articles were identified. Data evaluation synthesis: Scholarly literature including both qualitative and mixed methods primary research studies, that collected both qualitative and quantitative data, and some secondary research were identified for review. Articles were appraised for relevance by the researcher. Inductive thematic analysis and structured reporting was undertaken to synthesise the data. To ensure the rigor of articles Mixed Methods Appraisal Tool (MMAT) and Standard Quality Assessment Criteria for Evaluating Primary Research Papers (QualSyst) appraisals were undertaken. Out of the 216 articles, 15 research papers were identified as suitable for use within this review. Implications for practice: The review demonstrated that empirical data surrounding perioperative nursing staffing is widely available. Fatigue, perioperative nurse education and nurse-to-patient ratios have a significant impact on the safety of patients undergoing invasive procedures. However, there is a lack of quantitative data surrounding these staffing factors.